2010
DOI: 10.1002/ppap.200900090
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pH on Bacterial Inactivation in Aqueous Solutions due to Low‐Temperature Atmospheric Pressure Plasma Application

Abstract: Low‐temperature atmospheric pressure plasmas applied to the surface of an aqueous solution have been shown to be efficient bactericides for bacteria suspended in the solution, if the solution is sufficiently acidic. Especially of interest is the finding that there is a critical pH value of about 4.7 for the bactericidal effects, below which the bacteria are efficiently inactivated and above which the bacteria are hardly affected by the plasma application. It has been also found that the presence of superoxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
418
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 512 publications
(436 citation statements)
references
References 19 publications
18
418
0
Order By: Relevance
“…Since these compounds are considered as strong oxidizing agents, they react in air forming corrosive nitric acid and toxic organic nitrates. In water treatment using ozone generated by plasma discharge, these compounds play a key role in the decrease in the pH of the water [22], which affects the reactor performance to decompose pollutants [55]. Figure 12 shows typical FTIR spectra of the gas byproducts generated during the ozone production in the SDBD reactor at Vpp = 6 kV and different frequencies of 1, 3, , 5, and 10 kHz) in dry air.…”
Section: Nitrogen Byproductsmentioning
confidence: 99%
“…Since these compounds are considered as strong oxidizing agents, they react in air forming corrosive nitric acid and toxic organic nitrates. In water treatment using ozone generated by plasma discharge, these compounds play a key role in the decrease in the pH of the water [22], which affects the reactor performance to decompose pollutants [55]. Figure 12 shows typical FTIR spectra of the gas byproducts generated during the ozone production in the SDBD reactor at Vpp = 6 kV and different frequencies of 1, 3, , 5, and 10 kHz) in dry air.…”
Section: Nitrogen Byproductsmentioning
confidence: 99%
“…Plasma-activated liquid (PAL) including PAW is bacteriostatic against a number of microorganisms. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Its proposed high level of effectiveness in killing bacteria has earned it the nickname "water of death". 10) PAL has a good shelf-life with a reported retention of its antibacterial activity from days to weeks 7,15) to even years.…”
Section: Introductionmentioning
confidence: 99%
“…1,2) Plasma-activated water (PAW) is being investigated for the treatment of bacterial contamination on food products 3) and for medical applications. 4) The procedure is simple: water is treated with an electrically generated atmospheric plasma discharge before it is applied to the target.…”
Section: Introductionmentioning
confidence: 99%
“…This plasma is expensively known as "touchable plasma" whose electrical temperature is high and gas temperature is low [2,7]. So far, Kitano et al had reported [9,10] bacterial and protein inactivation as a plasma medicine utilizing this plasma irradiated liquid. It is difficult to apply this plasma to oral surgery (i.e., sterilization of biofilms at periodontal pocket, and removing the dental plaque in embrasure etc.)…”
Section: Introductionmentioning
confidence: 99%